2018
DOI: 10.1021/acsami.8b13159
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mechanical Degradation in Perfluoropolyether Film for Its Application to Antifingerprint Coatings

Abstract: Enhancing the mechanical durability of antifingerprint films is critical for its industrial application on touch-screen devices to withstand friction damage from repeated rubbing in daily usage. Using reactive molecular dynamics simulations, we herein implement adhesion, mechanical, and deposition tests to investigate two durability-determining factors: intrachain and interchain strength, which affect the structural stability of the antifingerprint film (perfluoropolyether) on silica. From the intrachain persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…9−11 Molecular dynamic simulations were often applied to determine the lubricity properties 12,13 as for silane-terminated PFPAE films to investigate the intrachain and interchain interactions in view of antifingerprint coatings. 14 This highlights the usefulness of the chemical modification of PFPAEs for lubricant applications as well as in confined spaces even in a simulated space environment. 15 However, even though their lubricant characteristics are their major advantage, high-performance thermoplastics and thermosets were fabricated after their chemical modification.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…9−11 Molecular dynamic simulations were often applied to determine the lubricity properties 12,13 as for silane-terminated PFPAE films to investigate the intrachain and interchain interactions in view of antifingerprint coatings. 14 This highlights the usefulness of the chemical modification of PFPAEs for lubricant applications as well as in confined spaces even in a simulated space environment. 15 However, even though their lubricant characteristics are their major advantage, high-performance thermoplastics and thermosets were fabricated after their chemical modification.…”
Section: Introductionmentioning
confidence: 90%
“…They also displayed better results than poly­(dimethylsiloxane) and poly­(butadiene) by combining low coefficient of frictions and a facilitated lateral motion . On the other hand, functionalized PFPAEs having four hydroxyl, cyclotriphosphazene, piperonyl, or even 3-phenylpropyl groups were examined depending on their adhesion, mobility, or humidity resistance properties and also compared to nonfunctionalized PFPAEs. Molecular dynamic simulations were often applied to determine the lubricity properties , as for silane-terminated PFPAE films to investigate the intrachain and interchain interactions in view of antifingerprint coatings . This highlights the usefulness of the chemical modification of PFPAEs for lubricant applications as well as in confined spaces even in a simulated space environment .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by studying the characterization of mechanical degradation in the perfluoropolyether film, Min et al found that, during the structural relaxation, OH in silane-functionalized perfluoropolyether (SPFPE) formed a H-bond with O on the SiO 2 , the Si−C bond in the chain simultaneously broke, and the end (C) of the broken residue formed a new bond with O in the silane agent (C−O bond). 52 Ahn et al indicated that each individual SPFPE molecule tended to be chemisorbed on the SiO 2 surface by forming a single siloxane bond, and the H-bond between the remaining silanol branches and the hydroxyl groups on the surface induced the shorter bond length of the first formed siloxane bond and then broke to form the second siloxane bond. 53 By comparing with the results, it is considered that the functional groups of OFMs easily interact with the surface silanol groups, and the H-bonds between polar groups and surface silanol groups (in Figure S3) would probably break and consequently facilitate the formation of new chemical bonds.…”
Section: ■ Methodologymentioning
confidence: 99%
“…The degradation rate depends on the length of polymer chains: short macromolecules like those in K100 have higher mobility (i.e., lower viscosity) which lead to higher degradation rates. Increasing the chain length can slow down degradation reactions (especially mechanical cleavage) [44], thus explaining the retention of amphiphobic properties of K105 and K107. It is also necessary to consider that abrasion tests cause friction and related increase in surface temperature; Krytox 100 is more susceptible to temperature increase than higher Krytox oils, with obvious negative effect on the amphiphobicity of K100.…”
Section: Response To Abrasionmentioning
confidence: 99%